A state-of-the-art review on pool boiling on nanostructure surfaces - Ignácio, Isabela [UNESP]; Cardoso, Elaine Maria [UNESP]; Gasche, José Luiz [UNESP]; Ribatski, Gherhardt (ASME International, 2015)
The differences in the heat transfer coefficient (HTC) and critical heat flux (CHF) behaviors between nanostructured and smooth surfaces are attributed to modifications on the surface wettability and capillarity effects through the porous matrix generated by the nanostructure layer. Both act in order of improving rewetting effects, explaining the CHF augmentation. The fact that the contact angle decreases is commonly considered to justify the HTC reduction for nanostructured surfaces. In this context, this study presents a critical review of the literature concerning the boiling phenomena on nanostructures surfaces. Care is exercised in order of characterizing the nanostructuring methods and compare heat transfer results obtained under almost similar conditions by different authors. Heat transfer mechanisms pointed in the literature as responsible for the heat transfer behaviors are also contrasted.